Profil Penggunaan Obat Antidotum Di Rumah Sakit Umum Daerah Undata Provinsi Sulawesi Tengah Periode 2016-2018: Profile of Using Antidotum at Undata General Hospital Central Sulawesi Province Periode of 2016-2018 - Mukaddas, Alwiyah; Faustine, Ingrid; Ulti, Putri Hijjah (Universitas Tadulako, 2019)
Antidotes drug is indicated in intoxication or poisoning patients, in addition to the antidote drugs, it can also be used as an appropriate therapeutic indication of his own medicine. The high increasing number of the antidote drug used every year in inpatient instalation Undata hospital, for exmple atropine, N-acetylcysteine and pyridoxine (vitamin B6). Therefore, this study aims to determine the percentage of drug use of antidote category indicated as an antidote therapy in Undata hospitals Central Sulawesi Province period 2016-2018. This is a descriptive study with retrospective approach and using purposive sampling techniques.The results showed that the sample size was 75 patients, with the percentage of drug use as antidotes category in Undata Hospital Central Sulawesi province period 2016-2018, namely pyridoxine (vitamin B6) of 49.33%, N-acetylcysteine drug of 42.66% and the atropine drug of 8%. The use of antidotes drug category are indicated as an antidote to the poisoning therapy drugs obtained 0%. It can be concluded that there is no antidote drug category that used as an antidote therapy on patients with drug poisoning in inpatient instalation Undata hospital Central Sulawesi Province Period 2016-2018.